Early plastic deformation behaviour and energy absorption in porous β-type biomedical titanium produced by selective laser melting. (August 2018) - Liu, Y.J.; Li, S.J.; Zhang, L.C.; Hao, Y.L.; Sercombe, T.B.
Abstract: Energy absorption is a critical consideration in the design of porous structures design. This work studied the energy absorption mechanism of three porous structures (i.e. cubic, topology optimised and rhombic dodecahedron) at the early stage of deformation. Stress distribution results, obtained by finite element modelling, coupled with the investigation of the slip bands generated have been used to reveal the plasticity mechanism and local stress concentrations for each structure. The topology optimised structure exhibits the best balance of bending and buckling stress with a high elastic energy absorption, a low Young's modulus ( 2.3 GPa) and a high compressive strength ( 58 MPa). Graphical abstract: Unlabelled Image